Nature and type of government and NGO interventions in curbing unemployment and underemployment of urban youth in Kenya - Simiyu, John; Sambu, Lenah (Journal of Emerging Trends in Educational Research and Policy Studies, 2012)
This paper examines nature and type of Government and NGO interventions in curbing youth unemployment and underemployment based on a study of the youth in Nairobi and Kisumu cities in Kenya. The study was descriptive in nature with a stratified sample from a population comprising respondents selected from slums of two major cities in Kenya where youth unemployment is rampant: Kibera slums in Nairobi and Manyatta slums in Kisumu. Questionnaires and interviews were the main research instruments used to gather data from the field for analysis. The sample size was determined by the number of registered youth groups in the slums. Data was analyzed by using descriptive statistics. Youth unemployment and underemployment is a crucial concern throughout the developing world, but it is a particularly acute problem in Africa where young people comprise a large proportion of the economically active population. Suffice to say, youth unemployment is highly dependent on the overall status of the economy. Economic activity, measured by GDP growth is probably the single factorthat most influences the chances of young people finding a job. In order to find a decent job in a globalized world, young people need to develop a range of skills and knowledge that are typically gained through formal education and training. African governments are implementing various policies and schemes to promote employment opportunities for young people, including skills training and entrepreneurship funds. Even if properly designed, however, the implementation of these interventions is constrained by cost and the lack of capacity among governments to evaluate the impact of policies. The study is useful to scholars and employment institutions in supplementing efforts by NGOs and the Government in dealing with the impact of youth unemployment and underemployment.
Keywords: ⛔ No DOI found